Inoculação de Azospirillum brasilense nas culturas de milho e trigo - Mello, Naiana de (2012)
The objective of this study was to evaluate the contribution of inoculation with Azospirillum sp. on yield and yield components in wheat and corn in interaction with nitrogen levels. Four experiments were conducted in the field at Agronomy and Veterinary Medicine College, Passo Fundo University. For all experiments it was used an experimental design of randomized blocks with four replications. In the field, two corn hybrids and one cultivar of wheat were tested. In corn experiment the treatments were with and without inoculation and nitrogen (N) topdressing fertilization, 0, 60, 90, 150 and 180 kg N ha-1 and the variables evaluated were: chlorophyll content in leaves, number of lines and grains per ear, ear weight, length and diameter, thousand-seed weight and yield. In wheat the treatments were with and without inoculation and nitrogen (N) topdressing fertilization, 0, 30, 60, 90 and 120 kg N ha-1. The variables evaluated were number of tillers, chlorophyll content in leaves, plant height, grain weight per ear, thousand-seed weight, hectoliter weight and yield. In corn there were interaction between hybrids and N levels on ear weight (in 2010/2011) and triple interaction on number of lines and grains per ear and yield. In wheat, there were interaction between inovulation and N levels on chlorophyll content (in 2011) and hectoliter weight (in 2010 and 2011). Inoculation had effect on yield in 2010. According the results, seed inoculation with Azospirillum brasilense strains AbV5 AbV6 do not influence plant growth and yield components of maize hybrids DKB 245 and AG 8025 and wheat cv. Marfim.